Strategies to Enhance Christian Community Trust through Spiritual Leadership and Public Service Quality, with Satisfaction as a Mediating Variable, at the Christian Community Guidance Division (Bimas Kristen) of the Ministry of Religious Affairs, Bangka Belitung Islands Province - Paulus Freddy Krissanjaya; Ari Agung Nugroho; Nizwan Zukhri; Rulyanti Susi Wardhani (Garuda Prestasi Nusantara Consulting, 2026)
This study aimed to analyze the effects of Spiritual Leadership and public service quality on congregational satisfaction and their impact on the trust of Christian congregants in the Christian Guidance Division of the Regional Office of the Ministry of Religious Affairs of the Bangka Belitung Islands Province. The study was motivated by the need for religious public services that not only emphasize administrative efficiency but also provide professional, humane, responsive, and spiritually grounded services to strengthen satisfaction and trust among service users. A quantitative approach with a survey method was employed in this study. The sample consisted of 395 Christian congregants in the Bangka Belitung Islands Province who had previously received services from the Christian Guidance Division. Respondents were selected using purposive sampling, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that Spiritual Leadership had a positive and significant effect on congregational satisfaction. Public service quality also positively and significantly influenced congregational satisfaction. Furthermore, both Spiritual Leadership and public service quality had positive and significant effects on Christian congregational trust. Congregational satisfaction was found to positively influence trust and significantly mediated the relationships between Spiritual Leadership, public service quality, and congregational trust. These findings suggest that strengthening effective Spiritual Leadership and improving service quality can enhance satisfaction and sustain public trust in religious public services.